Rekonstruksi Pedagogi "The Other" Emmanuel Levinas dalam PAK: Menjawab Fenomena Cyber-Bullying dan Intoleransi Digital di Era Disrupsi - Rahel Batong; Rifka Datukai Yang; Randan Randan; Eka Pertiwi Turu' Sambo; Asri Asri; Novi Belorundun (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2026)
The phenomena of cyberbullying and digital intolerance among young people are increasingly alarming in the era of technological disruption, and Christian Religious Education (CRE) is called to provide an adequate pedagogical response to this ethical crisis. This study aims to analyze the relevance of Emmanuel Levinas's ethics of responsibility toward the Other for the formation of students' digital character within CRE, and to formulate a pedagogical framework capable of transforming students' digital behavior from egocentric tendencies toward persons who uphold human dignity. A qualitative method with a library research design was employed, utilizing thematic content analysis of relevant academic sources. The findings indicate that Levinas's concepts of the face (le visage) and asymmetrical responsibility hold profound relevance for CRE, as they directly challenge the egocentric logic underlying destructive behavior in digital spaces. The pedagogical framework of CRE is formulated through three pillars: face-to-face pedagogy, alterity-based digital ethics literacy, and spirituality of responsibility as the foundation of transformation. The implications of this study affirm that CRE holds strategic potential to become a space for cultivating digital moral resilience, grounded in the affirmation of imago Dei and a transformative relational ethics.